THU0159 Rheumatoid arthritis may not influence eating behaviours characteristics. (15th June 2017) - Bulut, N; Tezcan, ME
Abstract : Background: Patients with rheumatoid arthritis (RA) have an increased risk of obesity and cardiovascular disease compared with the general population (1). Eating behaviours may play an important role in obesity and cardiovascular disease. Objectives: We hypothesised that RA patients have impaired eating behaviours that may have a role in obesity. For evaluating this hypothesis, we compared eating behaviours of patients with RA, osteoarthritis (OA) and healthy controls. Methods: One hundred and fifty-seven RA patients (M/F: 23/134) who fulfilled the 2010 American College of Rheumatology (ACR) RA classification criteria, 31 hand OA patients (M/F: 1/30) who fulfilled 1990 ACR hand OA criteria and 60 healthy controls (M/F: 9/51) were enrolled to the study who applied to Kartal Dr. Lutfi Kirdar Training and Research Hospital Rheumatology outpatient clinic. Eating behaviours was assessed by the Three-Factor Eating Questionnaire (TFEQ).Demographic data, smoking status, co-morbidities, anthropometric measurements, VAS pain score were analyzed. Results: There were no differences between three groups in demographic features and anthropometric measurements (table1 ). Moreover, there were no differences between three groups in cognitive restraint and emotional eating scores.Although, healthy controls had significantly higher uncontrolled eating scores than the RA group (p<0.05), uncontrolled eating scores of all three groups were lower than Turkish people average scores (2) (table2 ). Conclusions: This was the first study using the TFEQ in patients with RA. In our study, we found that disease features of RA may had no effect on eating behaviors. References: Kitas GD, Erb N. Tackling ischemic heart disease in rheumatoid arthritis. Rheumatology (Oxford). 2003;42(5):607–13. Kıraç D, Kaspar EÇ, Avcılar T, Çakır ÖK, Ulucan K, Kurtel H, ve ark. Obeziteyle ilişkili beslenme alışkanlıklarının araştırılmasında yeni bir yöntem "Üç Faktörlü Beslenme Anketi". MÜSBED. 2015;5(3):162–9. Acknowledgements: None. Disclosure of Interest: None declared